The instrument development for faculty readiness assessment on computational sustainability - Tuan Nurnadzirah Asyikin Tuan Rahim (Tanjong Malim, 2025)
The instrument development for faculty readiness assessment on computational sustainability by Tuan Nurnadzirah Asyikin Tuan Rahim